Outorga onerosa do direito de construir - Bosquesi, Ricardo (2006)
This one is about the created ground, instituted by the Federal Law nº 10,257, of July, 10th of 2001 - Statute of the City, as legal and politician institute adopted for the Urban Politics. Its structure, constituent elements, base and purposes are objects of inquiry of this work. It is analyzed the viability of its application, in the concretion of the general lines of direction proposals in the Statute of the City and principles contained in the Federal Constitution, relation to the control of the use of the ground and adequate ordinance of the cities. However, it serves to alert of the possibility of its disparagement, when absent a plan of institution and objective control, careful, impersonal and before everything, moral, by the City. Badly employee, will serve as an aggravation factor of the social inaqualities, allowing speculatives practices, socializing the losses and privatizing the decurrent profits of the urbanistic activity of the Public Power. Ahead of the normative quadrant of the Statute of the City in relation to the created ground (for being general norm), little can affirm concerning its efficiency, as legal and politician instrument of the Urban Politics. It will depend much more on the City, in the way that was structuralized the created ground, by its Managing Plan and specific City Law, the success or failure in the concretion of the objectives of the Urban Politics. Some aspects of the created ground had been left to the City so that they instituted them close to reality, in the scope of its discretional ability. In this point, important is the role of the doctrine and jurisprudence that are forming (has seen the recent normatization by the Statute of the City), so that they can offer parameters to guide its creation and improvement or, at least, to point the points that fatally will be able to lead to the purpose shunting line